2021
DOI: 10.3390/app11031104
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Production Process on the Anthocyanin Content and Composition in Dried Potato Cubes, Chips, and French Fries Made from Red-Fleshed Potatoes

Abstract: The stability of acylated anthocyanins is still a new and unexplored subject of study. The changes in the contents of individual anthocyanins in colored-flesh potato tubers during processing have rarely been addressed in the literature. The aim of the present study was to determine how anthocyanin degradation and profiles are influenced in potatoes of the red-fleshed Herbie 26 variety by different methods of processing. Potato samples were divided into four categories to be analyzed, namely, raw material, pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In Solanaceae, after the preliminary preparation procedures (cutting and/or crushing, homogenization, and peeling) which are responsible for the enzymatic oxidation processes with a partial decay of antioxidants, the critical step is represented by thermal processing [191,[196][197][198]. In tomato, during processing to produce tomato paste from fresh tomatoes, thermal treatment causes the breaking of protein aggregates where the pigment is associated inside the vegetable matrix, enhancing the carotenoid bioaccessibility [191].…”
Section: Impact Of Crop Management and Food Processing On Antioxidant...mentioning
confidence: 99%
“…In Solanaceae, after the preliminary preparation procedures (cutting and/or crushing, homogenization, and peeling) which are responsible for the enzymatic oxidation processes with a partial decay of antioxidants, the critical step is represented by thermal processing [191,[196][197][198]. In tomato, during processing to produce tomato paste from fresh tomatoes, thermal treatment causes the breaking of protein aggregates where the pigment is associated inside the vegetable matrix, enhancing the carotenoid bioaccessibility [191].…”
Section: Impact Of Crop Management and Food Processing On Antioxidant...mentioning
confidence: 99%
“…Kita et al [26] have studied on frying of red-and purplefleshed potatoes (Solanum tuberosum L.) that are a good source of anthocyanin and reported that frying process caused anthocyanin degradation of 38-70%. Rytel et al [27] found that at a temperature of 150°C, chips maintained 35% anthocyanin, while at higher temperature (170°C), the product maintained lower content (only about 16% original anthocyanin content in raw materials). The effect of frying on anthocyanin content in Hwajeon with the change ratio of black glutinous rice flour was studied by Jeonghee and Eunmi [28].…”
Section: Effect Of Added Extract Concentration and Frying Time On Ant...mentioning
confidence: 99%
“…The concentration and stability of these anthocyanins are affected by several parameters such as agronomic factors and postharvest storage. However, the stability of acylated anthocyanins is still not well addressed, and few studies in anthocyanins contents (CAT) in colored-flesh potato tubers during processing and digestion have been published [25,26]. The stability of anthocyanins is affected by pH, temperature, and light.…”
Section: Stability and Bioaccesibility: Potato Anthocyaninsmentioning
confidence: 99%
“…Chip products showed higher retention anthocyanins. Pelargonidin-3feruloylrutinoside-5-glucoside, and pelargonidin-3-caffeoylrutinoside-5-glucoside, were most thermally stable [25]. To reduce the loss of effectiveness of plant-based compounds as anthocyanins, and polyphenols from color fleshed potatoes, microencapsulation arise as an alternative.…”
Section: Red and Purple Flesh Potato-based Food And Natural Ingredients Responding To New Global Food Market Trendsmentioning
confidence: 99%